Towards performing high‐resolution inelastic X‐ray scattering measurements at hard X‐ray free‐electron lasers coupled with energetic laser drivers. (18th May 2022) - Descamps, A.; Ofori-Okai, B. K.; Baldwin, J. K.; Chen, Z.; Fletcher, L. B.; Glenzer, S. H.; Hartley, N. J.; Hasting, J. B.; Khaghani, D.; Mo, M.; Nagler, B.; Recoules, V.; et al.
Abstract : High‐resolution inelastic X‐ray scattering measurements at hard X‐ray free‐electron lasers coupled with energetic laser drivers have shown a 2.5‐fold improved energy resolution compared with previous experiments at similar XFEL instruments. Aspects of the experimental design that can be adjusted to improve the number of recorded photons on the detector are discussed. Abstract : High‐resolution inelastic X‐ray scattering is an established technique in the synchrotron community, used to investigate collective low‐frequency responses of materials. When fielded at hard X‐ray free‐electron lasers (XFELs) and combined with high‐intensity laser drivers, it becomes a promising technique for investigating matter at high temperatures and high pressures. This technique gives access to important thermodynamic properties of matter at extreme conditions, such as temperature, material sound speed, and viscosity. The successful realization of this method requires the acquisition of many identical laser‐pump/X‐ray‐probe shots, allowing the collection of a sufficient number of photons necessary to perform quantitative analyses. Here, a 2.5‐fold improvement in the energy resolution of the instrument relative to previous works at the Matter in Extreme Conditions (MEC) endstation, Linac Coherent Light Source (LCLS), and the High Energy Density (HED) instrument, European XFEL, is presented. Some aspects of the experimental design that are essential for improving the number of photons detected in each X‐ray shot, making such measurements feasible, are discussed. A careful choice of the energy resolution, the X‐ray beam mode provided by the XFEL, and the position of the analysers used in such experiments can provide a more than ten‐fold improvement in the photometrics. The discussion is supported by experimental data on 10 µm‐thick iron and 50 nm‐thick gold samples collected at the MEC endstation at the LCLS, and by complementary ray‐tracing simulations coupled with thermal diffuse scattering calculations.